Polityka wyznaniowa Koreańskiej Republiki Ludowo-Demokratycznej w latach 1994–2023. Próba zrozumienia zagadnienia - Bielicki, Paweł (Studia Polityczne, 2024)
The main goal of my article will be to analyze North Korea’s religious policy from the death of Kim Il-sung to the present. I intend to take a closer look at the views of Polish and foreign researchers on this matter, focusing especially on the aspirations of the Kim dynasty towards divine worship. At the beginning, I would like to present the theoretical aspects of religious policy, paying particular attention to the definition of the above term and its most important methodological assumptions. In this respect, it will be important to describe the problem of religious freedom. Then I try to trace the times of reign of individual Korean dynasties that referred to Confucianism. In the further part of my considerations, I present the aggressive anti-religious campaign of the North Korean communists, who, among others, Juche ideology has been striving for total mind control of the country’s inhabitants since the 1950s, which was visible in the cult of the first leader of the DPRK, Kim Il-sung. I also touch on the problem of a certain softening of the rhetoric towards religion at the turn of the 1980s and 1990s, manifested in the existence of facade churches to improve the country’s image on the international arena. In conclusion, I intend to answer the question of how the religious policy of the DPRK has evolved over the decades. Moreover, it will be important to answer the question of what role religion played in shaping the Kim dynasty, which still rules North Korea to this day.